A novel homozygous SLC39A14 variant in an infant with hypermanganesemia and a review of the literature - Zhang, Meijiao; Zhu, Liping; Wang, Huiping; Hao, Ying; Zhang, Qingping; Zhao, Chunyan; Bao, Xinhua (Frontiers in Pediatrics, 2023)
Background: Manganese (Mn) is an essential trace metal necessary for good health; however, excessive amounts in the body are neurotoxic. To date, 3 genes SLC30A10, SLC39A8, and SLC39A14 had been discovered to cause inborn errors in Mn metabolism in humans. As very rare diseases, the clinical features require further clarification. Methods: A male Chinese patient who mainly presented with hypermanganesemia and progressive parkinsonism–dystonia was recruited for this study. We collected and analyzed clinical information, performed whole-exome sequencing (WES), and reviewed relevant literature. Results: The motor-developmental milestones of the patient were delayed at the age of 4 months, followed by rapidly progressive dystonia. The patient displayed elevated Mn concentrations in blood and urine. Brain magnetic resonance imaging (MRI) showed symmetrical hyperintensity on T1-weighted images and hypointensity on T2-weighted images in multiple regions. A novel homozygous variant in SLC39A14 gene (c.1058T>G, p.L353R) was identified, and the patient was administered disodium calcium edetate chelation (Na2CaEDTA) therapy. After 3 months of treatment, mild improvement in clinical manifestation, blood Mn levels, and brain MRI were observed. To date, 15 patients from 10 families have been reported with homozygous mutations of SLC39A14, with a mean age of onset at 14.9 months. The common initial symptom was motor regression or developmental milestone delay. Towards the course of disease, nearly all the patients developed progressive generalized dystonia and lost ambulation before treatment. Additionally, the hypermanganesemia was with values 4 to 25 times higher than that of normal. The characteristics of brain MRI results were similar to those observed in the recruited patient. Nine SLC39A14 variants have been identified. Seven patients have been treated with Na2CaEDTA and only one patient achieved obvious clinical improvement. Conclusion: We identified a novel SLC39A14 mutation related to autosomal recessive hypermanganesemia with dystonia-2, which is a very rare disease. Patients present motor regression or delay of developmental milestones and develop progressive generalized dystonia finally. Chelation therapy with Na2CaEDTA appears to effectively chelate Mn and increase urinary Mn excretion in some cases; however, clinical response varies. The outcome of the disease was unsatisfied. This study expands the clinical and genetic spectrum of this disease